Training Moral Sensitivity Through Video Games: A Review of Suitable Game Mechanisms. Issue 4 (June 2019) - Katsarov, Johannes; Christen, Markus; Mauerhofer, Ralf; Schmocker, David; Tanner, Carmen
The goal of this study is to support game designers in the selection and implementation of game mechanisms to promote players' moral sensitivity (MS). A lack of MS may lead people to behave unethically, without awareness for their actions' moral implications. In this study, we conduct a theory-based evaluation of 20 distinct game mechanisms in view of their potential to promote MS. MS is thereby operationalized in terms of three learning outcomes (LOs): empathic concern for relevant groups, alertness to values/principles, and awareness for one's vulnerability to biases. This study suggests that MS is best promoted through a careful combination of game mechanisms, addressing all three LOs.